Study on the use of 3‐aminopropyltriethoxysilane and 3‐chloropropyltriethoxysilane to surface biochemical modification of a novel low elastic modulus Ti–Nb–Hf alloy. Issue 3 (9th June 2014) - Paredes, V.; Salvagni, E.; Rodríguez‐Castellon, E.; Gil, F. J.; Manero, J. M.
Abstract: A biocompatible new titanium alloy Ti–16Hf–25Nb with low elastic modulus (45 GPa) and the use of short bioadhesive peptides derived from the extracellular matrix have been studied. In terms of cell adhesion, a comparative study with mixtures of short peptides as RGD (Arg‐Gly‐Asp)/PHSRN (Pro‐His‐Ser‐Arg‐Asn) and RGD (Arg‐Gly‐Asp)/FHRRIKA (Phe‐His‐Arg‐Arg‐Ile‐Lys‐Ala) have been carried out with rat mesenchymal cells. The effect of these mixtures of short peptides have already been studied but there are no comparative studies between them. Despite the wide variety of silane precursors available for surface modification in pure titanium, the majority of studies have used aminosilanes, in particular 3‐minopropyltriethoxysilane (APTES). Nevertheless, the 3‐chloropropyltriethoxysilane (CPTES) is, recently, proposed by other authors. Unlike APTES, CPTES does not require an activation step and offers the potential to directly bind the nucleophilic groups present on the biomolecule (e.g., amines or thiols). Since the chemical surface composition of this new alloy could be different to that pure titanium, both organosilanes have been compared and characterized by means of a complete surface characterization using contact angle goniometry and X‐ray photoelectron spectroscopy. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B:495–502, 2015.